2019
DOI: 10.3390/d11090141
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography, Systematics, and Ecomorphology of Pacific Island Anoles

Abstract: : Anoles are regarded as important models for understanding dynamic processes in ecology and evolution. Most work on this group has focused on species in the Caribbean Sea, and recently in mainland South and Central America. However, the Eastern Tropical Pacific (ETP) is home to seven species of anoles from three unique islands (Islas Cocos, Gorgona, and Malpelo) that have been largely overlooked. Four of these species are endemic to single islands (Norops townsendi on Isla Cocos, Dactyloa agassizi on Isla Mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…Island isolation was significant in models for five taxonomic groups: single‐island endemic plants (SIE_P), both vertebrate groups, reptiles and birds. While birds are the most obvious taxa to disperse between islands, lizards are often hypothesized and occasionally observed to disperse to oceanic islands through rafting (Censky et al, 1998; Phillips et al, 2019; Raia et al, 2017), and while Galápagos tortoises are poor swimmers, they can float and survive without food for an extended period of time (Caccone et al, 2002), allowing dispersal to proximate islands. Therefore, the degree of isolation for these groups makes sense as a predictor of species richness while native mammals (mostly from endemic radiation of muroid rats [Schenk & Steppan, 2018]) and low‐dispersing invertebrates (including snails, discussed below) may be more impacted by intra‐island factors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Island isolation was significant in models for five taxonomic groups: single‐island endemic plants (SIE_P), both vertebrate groups, reptiles and birds. While birds are the most obvious taxa to disperse between islands, lizards are often hypothesized and occasionally observed to disperse to oceanic islands through rafting (Censky et al, 1998; Phillips et al, 2019; Raia et al, 2017), and while Galápagos tortoises are poor swimmers, they can float and survive without food for an extended period of time (Caccone et al, 2002), allowing dispersal to proximate islands. Therefore, the degree of isolation for these groups makes sense as a predictor of species richness while native mammals (mostly from endemic radiation of muroid rats [Schenk & Steppan, 2018]) and low‐dispersing invertebrates (including snails, discussed below) may be more impacted by intra‐island factors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Among vertebrates, the putative endemics include the catfish Trichomycterus gorgona Fernández & Schaefer, 2005, the anoles Anolis gorgonae Barbour, 1909 and A. medemi Ayala & Williams, 1988 ( Phillips et al 2019 ), the snake Atractus medusa Passos et al, 2009 , and an undescribed species of dendrobatid frog reported as “ Colostethus sp. Gorgona” by Grant et al (2017) .…”
Section: Introductionmentioning
confidence: 99%
“…I also expected that distance from the continent would be correlated with a greater presence of endemic species (Kougioumoutzis & Tiniakou, 2015). Marine channels, even if they are relatively shallow, can constitute an almost impassable barrier for some small lizards (Hurston et al., 2009), although there are also opposite examples (Phillips et al., 2019; Raia et al., 2017). Consequently, I hypothesized that isolation relative to other islands in an archipelago would be negatively associated with both groups of lizards.…”
Section: Introductionmentioning
confidence: 99%